Early Initiation of Breastfeeding: Caesarean Mother’s Challenges and Coping - Mussarat Musera Khan; Mamta Verma; Rajratn Gupta (Pediatric Review: International Journal of Pediatric Research, 2025)
The aim of this narrative review is to identify the available literature related to factors related to caesarean section and early initiation of breastfeeding, challenges which cause hinderance to early initiation of breastfeeding and the coping strategies mothers could employ to overcome the challenges. The narrative review secondarily helps the author to select the study design, methodology and development of the questionnaire. It is a well-known fact that early initiation of breastfeeding is essential component in the crucial first hour after birth. The review compares the data obtained through various searches in regard to early initiation of breastfeeding in vaginal and caesarean delivery. Also, some factors which are responsible for delay especially in case of caesarean section are identified which would help in planning of assessment questionnaire components. Apart from caesarean section delivery being the main determinant for late initiation of breastfeeding, the associated clues like post- operative pain, delayed mother-newborn dyad contact, lack of maternal efficiency to handle newborn after birth plays an important role in determining the breastfeeding initiation. Family and partner support had a great role in coping with post- partum anxiety.Key words: early initiation of breastfeeding (EIBF), caesarean section, vaginal delivery, challenges, coping strategies